Investigation on multiscale features of cavitating flow in convergent-divergent test section using Eulerian–Lagrangian method. (15th January 2023) - Wang, Zhengdong; Li, Linmin; Li, Xiaojun; Zhu, Zuchao; Yang, Shunyin; Yang, Guojun
Highlights: An Eulerian–Lagrangian multiscale model is proposed for cavitating flow. A two-way transition algorithm is developed for bridging micro and macro scales. Multiscale cavitation features are well predicted by the VOF-DBM model. The VOF-DBM model is found less sensitive to the mesh resolution. Abstract: Cavitating flows in fluid machineries always present complicated phase morphologies including a wide range of interface length scales. In the present work, an Eulerian–Lagrangian cavitation model is proposed for simulating the unsteady cavitating flow and investigating the multiscale cavitating flow features in a convergent-divergent test section. Most importantly, a two-way transition algorithm is newly developed mainly based on the shape of resolved cavities and the relative size of microscale bubbles compared to the cells, for taking the transition between microscale discrete bubbles and macroscale vapor cavities into consideration. The transient flow field of the two-phase system is described by the filtered Navier–Stokes equation and the sub-grid scale model. The volume of fluid (VOF) method and a discrete bubble model (DBM) are combined for simulating resolvable water-vapor interfaces and unresolvable discrete bubbles, respectively. Applying the proposed multiscale modeling framework, the dissipated bubbles caused by the collapse of shedding cavities that are unable to be represented by the VOF method are well predicted. The results show that the VOF-DBM model is less sensitive to the mesh resolution compared to the VOF method and it is found the dissipated bubbles are transporting around the vortex core region. Detailed bubble dynamics including DBM to VOF and VOF to DBM transitions and the interaction between macroscale cavities and microscale bubbles are well presented, indicating that the proposed VOF-DBM model is a promising approach to reveal the multiscale cavitation characteristics within limited computing resources. Graphical abstract: The multiscale cavitation model, predicted two-way transition between VOF and DBM, multiscale cavitation features and bubble-flow interactions. Image, graphical abstract